Bio fuels for compression ignition engine: A review on engine performance, emission and life cycle analysis. (November 2016) - Patel, Paresh D.; Lakdawala, Absar; Chourasia, Sajan; Patel, Rajesh N.
Abstract: As an alternative fuel for compression ignition engines, biofuels are in principal renewable and carbon unbiased. However, their use raises technical, economical and environmental issues. A complete technical review on the use of biofuel (pure oil/blend with diesel/blend with diesel in the presence of additives) in CI engines based on performance and emission comparisons with diesel fuel is carried out in this work. It is observed that biofuel seems to be a good option to substantially reduce environmental emissions. Although the majority of biofuels can be used in CI engine without any modifications, change in operating parameters (injection timing, injection pressure & compression ratio) is advisable for improvement in engine performance. Moreover, short run studies show that biofuels have great potential to replace conventional diesel fuel, the review suggests that biofuels produce a various problem when used for extended period of times. Especially, in this study particular attention is focused on the long run test (life cycle analysis) of CI engine fuelled with biofuels. The study suggests that use of biofuels produces various tribological issues on key components of CI engine. In the literature the tribological studies were discussed with atomic absorption spectroscopy, surface roughness analysis, wear analysis, close microscopic image analysis etc. of the CI engine components. Graphical abstract: Highlights: A technical review on suitability of bio fuels for CI engine is carried out. Review suggests that engine operating parameters are required to be change. Plant oil based long run test suggests engine suffers from tribological issues. Use of biofuels and additives reduces tribological problems during long run.